Association of Dietary Magnesium Intake With Leukocyte Telomere Length in United States Middle-Aged and Elderly Adults - Hu, Lihua; Bai, Yi; Hu, Guiping; Zhang, Yan; Han, Xiaoning; Li, Jianping (Frontiers in Nutrition, 2022)
Aim: Magnesium supplementation may extend the life span; however, the biological mechanism is still unknown. Leukocyte telomere length (LTL) is a marker of cell aging and biological health in humans. Data concerning whether magnesium supplementation can maintain telomere length, thus prolonging life are limited. We aimed to investigate the association between dietary magnesium intake and LTL in US middle-aged and elderly adults. Methods: A total of 4039 US adults aged ≥45 years from National Health and Nutrition Examination Survey (NHANES, 1999-2002). Dietary magnesium intake was collected by a trained interviewer using 24-hour dietary recall method and LTL was obtained using the quantitative polymerase chain reaction (PCR) method. Multiple linear regression analysis was performed to evaluate the crude and adjusted association of dietary magnesium intake with LTL. Results: The overall mean (SD) of LTL was 5.6 (0.6) kp. After adjusting potential confounders, every 1 mg increase in log-transformed dietary magnesium intake was associated with 0.20 kp [95% confidence intervals (CI): 0.05-0.34] longer LTL. Participants with the highest tertile (≥ 299 mg) of dietary magnesium intake had statistically significant longer LTL (β = 0.07, P = 0.038) compared with the lowest tertile (< 198 mg), with significant linear trends across tertiles. Moreover, the association between dietary magnesium intake and LTL was significantly stronger in participants with higher levels of education (≥ high school compared with < high school, P for interaction = 0.002). E-value analysis suggested robustness to unmeasured confounding. Conclusions: Our findings showed that increased dietary magnesium intake was associated with longer LTL, which suggested that magnesium was conducive to a longer life expectancy.